Pengembangan Infrastruktur Jaringan Untuk Meningkatkan Pelayanan Publik di Kota Palembang - Darius Antoni; Muhammad Izman Herdiansyah; Muhamad Akbar; Agus Sumitro (STMIK Budi Darma, 2021)
Technological advances will always develop following the progress of science. Internet technology has a great influence in every aspect, especially in the implementation of the service function of the Government to every citizen in need. The Publik Service Sector deals with communities in need with the government as a service-providing institution. The government is required to be able to keep up with the development of technology in service to the community more effectively, efficiently, quickly and accurately. With the internet network technology can be used to build an electronic-based government service system or E-Government. The use of information technology can change the pattern of publik services in reducing corruption, financial transparency, convenience of services and increasing revenue in each region. However, each region with its own geographical conditions of course there are still people in the lower middle class or the poor who have not been able to access publik services of their government, So in this thesis, researchers are interested in developing network infrastructure design so that people in villages or villages, especially RT who have minimal access, can enjoy publik services in Palembang City